2014
DOI: 10.1080/17461391.2014.969325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute L‐Alanyl‐L‐Glutamine and electrolyte ingestion on cognitive function and reaction time following endurance exercise

Abstract: The purpose of this study was to examine the effect of the L-Alanyl-L-Glutamine dipeptide (AG) on cognitive function and reaction time (RT) following endurance exercise. Twelve male endurance athletes (23.5 ± 3.7 y; 175.5 ± 5.4 cm; 70.7 ± 7.6 kg) performed four trials, each consisting of running on a treadmill at 70% of VO2max for 1h, then at 90% of VO2max until exhaustion. One trial consisted of no hydration (DHY), another required ingestion of only a sports electrolyte drink (ED) and two trials required inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…For example, amateur soccer players who ingested 5 g of glutamine in a multi-ingredient supplement experienced attenuated perceived fatigue after a 90 min intermittent sprint test [18]. In addition, acute rehydration with an L-alanyl-L-glutamine drink improved reaction time after exhaustive treadmill running [50]. Similar to the current study, we recently reported that oral glutamine prior to, and after firefighting simulations increased HSP70, which aligned with lower subjective fatigue on the second day of physical work [51].…”
Section: Discussionmentioning
confidence: 99%
“…For example, amateur soccer players who ingested 5 g of glutamine in a multi-ingredient supplement experienced attenuated perceived fatigue after a 90 min intermittent sprint test [18]. In addition, acute rehydration with an L-alanyl-L-glutamine drink improved reaction time after exhaustive treadmill running [50]. Similar to the current study, we recently reported that oral glutamine prior to, and after firefighting simulations increased HSP70, which aligned with lower subjective fatigue on the second day of physical work [51].…”
Section: Discussionmentioning
confidence: 99%
“…Two years later, the same research group reported that rehydration with L-alanyl-L-glutamine after 2.3% dehydration in a basketball scrimmage led to an improvement in basketball skill performance and visual reaction time when compared to water [ 525 ]. A 2016 study indicated that L-alanyl-L-glutamine maintained reaction time in an upper and lower-body activities after an exhaustive bout of treadmill running [ 526 ]. Finally, a 2015 paper determined that L-alanyl-L-glutamine significantly improved treadmill running performance when compared to no hydration [ 527 ].…”
Section: Introductionmentioning
confidence: 99%
“…The shuffle reaction ball drill with a higher score showed a significant difference compared to the side shuffle drill. Shuffle reaction ball drill is an exercise to increase reaction time and dexterity skills by using a stimulus about the sense of response to seeing [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%